Towards a moss sclerophylly continuum: Evolutionary history, water chemistry and climate control traits of hygrophytic mosses. (10th September 2019) - Fernández‐Martínez, Marcos; Berloso, Ferran; Corbera, Jordi; Garcia‐Porta, Joan; Sayol, Ferran; Preece, Catherine; Sabater, Francesc
Abstract: Mosses are amongst the oldest and simplest plants, they can be found almost everywhere in the world, and they condition the structure and function of many ecosystems. Their sensitivity to environmental changes makes them very interesting subjects of study in ecology, and understanding them can provide insights into the evolutionary history of plants. However, the study of moss traits and their relationship with their environment is far behind that of vascular plants. We sampled 303 assemblages of aquatic and semi‐aquatic (hygrophytic) mosses growing in semi‐natural springs distributed around the northeast of the Iberian Peninsula to study how moss traits vary depending on their evolutionary history, climate and water chemistry. To do so, we analysed 30 moss species and 17 traits using phylogenetic comparative methods and an extended RLQ analysis, accounting for spatial and phylogenetic information. We hypothesized that there is a sclerophylly continuum in mosses living across a gradient of high and low water conductivity springs that may mimic sclerophylly in vascular plants that live in stressful environments. Results indicated that life‐forms and, especially, morphological traits were well preserved phylogenetically and responsive to water chemistry and climate. That combined with spatial autocorrelation in environmental variables resulted in a clustered distribution of phylogenetically closely related mosses in space. Mosses living in springs with a warm and dry climate that discharge hard water mainly presented species with needle‐like leaves, were denser, and had lower water absorption capacity. The opposite was found in cold, humid and soft water springs. Synthesis . Our results suggest that climate and water chemistry are main determinants of traits of hygrophytic mosses and of species distributions. We found evidence of a potential sclerophylly continuum in moss traits, which we hypothesize may be mainly related to physical and physiological constraints produced by water chemistry. Our findings describe moss sclerophylly in a gradient of water conductivity similar to that found in vascular plants with water availability and temperature. Further experimental studies will be required to confirm the observations found in this study. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Abstract (Catalan ‐ Català): Les molses són les plantes més simples i antigues. Gairebé arreu del món condicionen l'estructura i el funcionament dels ecosistemes. Llur sensibilitat als canvis ambientals fa que el seu estudi sigui d'especial rellevància en el camp de l'ecologia, aportant coneixements molt valuosos sobre la història evolutiva de les plantes. Tanmateix, l'estudi de les molses i les relacions d'aquestes amb l'ambient resta encara a les beceroles en comparació amb les plantes vasculars. Es van mostrejar 303 comunitats de molses aquàtiques i semi‐aquàtiques (higrofítiques), que habitaven fonts semi‐naturals de Catalunya, per estudiar com els trets de les molses variaven segons la seva història evolutiva, el clima i la química de l'aigua de les fonts on es trobaven. Es van analitzar 30 espècies de molses i 17 trets fent servir mètodes filogenètics i un anàlisi RLQ, incorporant informació espacial i filogenètica. La nostra hipòtesi era que, en molses higrofítiques, existeix un gradient d'esclerofília que opera a través d'un gradient de conductivitat de l'aigua de les fonts, de forma similar al que trobem en les plantes vasculars que viuen en ambients estressants. Els resultats indiquen que les formes de vida i els trets morfològics de les molses estan ben preservats filogenèticament i que varien seguint els gradients de conductivitat de l'aigua i del clima. Aquest fet combinat amb l'autocorrelació espacial en les variables ambientals, resulta en una distribució agregada en l'espai de les espècies més properes filogenèticament. Les molses que viuen en fonts de clima càlid i sec i de les quals brolla aigua d'alta conductivitat tendeixen a ser més denses, absorbir menys aigua i a tenir fil·lidis més allargassats. La tendència oposada es troba en fonts de clima fred, humit i amb aigua de baixa conductivitat. Síntesi : Els nostres resultats suggereixen que el clima i la química de l'aigua determinen els trets de les molses higrofítiques i llurs distribucions. Hem trobat evidències d'un potencial gradient d'esclerofília en els trets de les molses que hipotetitzem que està relacionat amb els constrenyiments físics i fisiològics imposats per la química de l'aigua de les fonts. Seran necessaris treballs experimentals per a confirmar les observacions trobades en aquest estudi.